Democracy and Exclusion from Suffrage - Jentsch, Sabine (Momentum Quarterly, 2013)
In some situations, the German legislator denies citizens the right to vote, which affects especially people who are subject to so-called „full custodianship“. As the author argues, however, the corresponding legislation fails to be legitimate. It both violates the political right to democratic participation of the excluded minority and puts at stake the democratic self-conception of the community as a whole. In its attempt to justify the relevant legislation, the German legislator relies on a morally and legally problematic conception of democracy that construes the basic democratic right to vote as a „natural“ or „performance-based“ privilege. Yet this undermines important interconnections between human rights and civil rights that are constitutive for modern democracies